Intelligent marking system for structured question/ Mastura Ariffin - Mastura, Ariffin (2002)

(untitled)
As part of the graduation exercise, it is required to develop as system for the Degree of Bachelor in Computer Science and Information Technology, University of Malaya. The system is intended to develop an Intelligent Marking System for Structured Question. The Intelligent Marking System hopes to overcome the manual marking that are done for many years. The Intelligent Marking System aims to give a fast response and marks to the answer that are answered . The literature review gives an overview of the marking system and findings of various researches and technology in the effectiveness of the intelligent marking system. Some of the literature surveys done are examined and their features compared. In this project, sources were collected from various part including the Internet ,books and the senior project. The Intelligent Marking System developed through a modified version combining the benefits of both waterfall model and prototyping approach. The Artificial Intelligence technique,such as The Expert System- The Rule Based System,The Information Retrieval and keyowrd matching used for the developing tools for the Intelligent Marking System while the software used is JBuilder 5. The selection of both hardware and software are vital to ensure the success of a system. Criteria such as capability, credibility, cost speed and size of memory have been emphasized to ensure the hardware-selected meet the requirements of the system to be developed.